Optimising the delivery of remediation programmes for doctors: a realist review - Price, T; Wong, G; Withers, L; Wanner, A; Cleland, J; Gale, T; Prescott‐Clements, L; Archer, J; Bryce, M; Brennan, N (Wiley, 2021)
Context: Medical underperformance puts patient safety at risk. Remediation, the process which seeks to “remedy” underperformance and return a doctor to safe practice, is therefore a crucially important area of medical education. However, while remediation is used in healthcare systems globally, there is limited evidence for the particular models or strategies employed. The purpose of this study was to conduct a realist review to ascertain why, how, in what contexts, for whom and to what extent, remediation programmes for practising doctors work to restore patient safety.